“Biar Gampang Urusannya”: Pergulatan Rekognisi Pernikahan Adat Suku Asli Anak Rawa, Riau, Indonesia: To Avoid the Hassle”: Customary Marriage Recognition Struggles of the Anak Rawa Tribe in Riau, Indonesia - Bambang Hermanto; Mohd.Habibi; Laila Sari Masyhur; Muhammad Ansor; Imam Hanafi (Al-Adabiya: Jurnal Kebudayaan dan Keagamaan, 2025)
The Indonesian Constitutional Court Decision No. 97/PUU-XIV/2016 has created a legal space for penghayat kepercayaan (adherents of indigenous beliefs) to register their identities in official population documents. However, the implementation of this recognition continues to face significant bureaucratic and social barriers. This study explores the struggle for legal recognition of customary marriages among the Anak Rawa indigenous community in Siak Regency, Riau. Employing a qualitative approach, the research draws on in-depth interviews, participatory observation, and document analysis. Findings reveal that despite normative legal recognition, implementation remains limited and fragmented at the local level. Many community members feel compelled to convert to state-recognized religions to gain access to civil rights, such as marriage certificates and birth registration for their children. Structural pressures, social stigma, and a legal-administrative system biased toward official religions undermine the ability of indigenous faith communities to preserve their identity. Key challenges include limited information dissemination, a lack of technical guidance for local civil registration officers, and weak institutional coordination. The study emphasizes the importance of a multi-sectoral approach that involves government institutions, civil society, and academia in promoting inclusive and sustainable legal recognition. Effective advocacy strategies include disseminating regulations, empowering communities, and engaging in interfaith dialogue to reduce social resistance. Ultimately, the legal recognition of customary marriage is not merely an issue of administrative formality, but a broader struggle for the cultural and civil rights of indigenous belief communities in Indonesia.